2017
DOI: 10.1038/s41523-017-0033-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in ER+ HER2 -node-positive breast cancer patients who were treated according to the Recurrence Score results: evidence from a large prospectively designed registry

Abstract: The Recurrence Score® is increasingly used in node-positive ER+ HER2-negative breast cancer. This retrospective analysis of a prospectively designed registry evaluated treatments/outcomes in node-positive breast cancer patients who were Recurrence Score-tested through Clalit Health Services from 1/2006 through 12/2011 (N = 709). Medical records were reviewed to verify treatments/recurrences/survival. Median follow-up, 5.9 years; median age, 62 years; 53.9% grade 2; 69.8% tumors ≤ 2 cm; 84.5% invasive ductal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
75
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 28 publications
3
75
1
Order By: Relevance
“…The identification of patients with high clinical risk and low genomic score with at least a 92.5% chance of being free of distant metastasis without chemotherapy at 5 years was demonstrated using the Mammaprint assay in the MINDACT trial . Prospective outcomes in >60,000 patients (including both clinical and epidemiological data) treated based on 21‐gene assay results have shown that patients within the low RS group (RS < 18) have excellent outcomes without chemotherapy . The prognostic power of the RS was validated in an endocrine‐treated NSABP B14 cohort, in the Kaiser Permanante, JBCRG, SWOG 8814 and in the transATAC studies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of patients with high clinical risk and low genomic score with at least a 92.5% chance of being free of distant metastasis without chemotherapy at 5 years was demonstrated using the Mammaprint assay in the MINDACT trial . Prospective outcomes in >60,000 patients (including both clinical and epidemiological data) treated based on 21‐gene assay results have shown that patients within the low RS group (RS < 18) have excellent outcomes without chemotherapy . The prognostic power of the RS was validated in an endocrine‐treated NSABP B14 cohort, in the Kaiser Permanante, JBCRG, SWOG 8814 and in the transATAC studies .…”
Section: Introductionmentioning
confidence: 99%
“…21 Prospective outcomes in >60,000 patients (including both clinical and epidemiological data) treated based on 21-gene assay results have shown that patients within the low RS group (RS < 18) have excellent outcomes without chemotherapy. [32][33][34][35][36][37][38] The prognostic power of the RS was validated in an endocrine-treated NSABP B14 cohort, in the Kaiser Permanante, JBCRG, SWOG 8814 and in the trans-ATAC studies. 2,9,11,23,24,39 The predictive power of RS for the prediction of chemotherapy benefit was initially validated in the NSABP B20 study in endocrine only vs. chemoendocrinetreated cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…In a different nonrandomized study of 709 patients who had pN1 lymph node status with micrometastases (pN1mic) (n = 298) or pN1 breast cancer from the Israeli Clalit Health Services registry, chemotherapy was associated with a lower Cancer January 15, 2019 distant recurrence rate in those who had a RS from 18 to 30 (1.0% vs 9.7%; P = .02). 13 This chemotherapy benefit was not observed for those who had a RS <18 (n = 379), although only 27 patients (7%) received chemotherapy in that group. Although data from those nonrandomized studies should be interpreted with caution, they also support the idea that the RS may identify a subgroup of patients with lymph node-positive breast cancer for whom chemotherapy is not warranted.…”
mentioning
confidence: 89%
“…In multivariable analysis, the number of positive lymph nodes and RS category were independent predictors of breast cancer‐specific survival. In a different nonrandomized study of 709 patients who had pN1 lymph node status with micrometastases (pN1mic) (n = 298) or pN1 breast cancer from the Israeli Clalit Health Services registry, chemotherapy was associated with a lower distant recurrence rate in those who had a RS from 18 to 30 (1.0% vs 9.7%; P = .02) . This chemotherapy benefit was not observed for those who had a RS <18 (n = 379), although only 27 patients (7%) received chemotherapy in that group.…”
mentioning
confidence: 99%
“…However, discordance between clinical risk defined by tumor grade and genomic risk defined by RS has been demonstrated in up to 30% of patients in other datasets of both node-negative and node-positive patients, highlighting the potential for genomic assays to refine prognosis beyond traditional clinicopathologic factors. [4][5][6] After a median follow-up of 57 months, there were significant differences among RS risk groups with respect to breast cancer-specific survival (BCSS) and overall survival (OS). Multivariate analysis showed that both RS risk group and the AJCC pathologic prognostic stage were independent prognostic factors for BCSS and OS.…”
mentioning
confidence: 99%